(untitled) (Economics and region, 2021)
The article deals with the problems of environmental accounting. It is very important, because the scale of environmental problems, increasing environmental pollution requires management to eliminate them and encourage them to seek environmental and economic management tools based on sustainable development. One of the main tools designed to solve this problem at the level of the business entity is the scientific development and formulation of environmental accounting. To date, there is no single established system for the implementation and operation of this type of accounting, which can lead to violations of informing interested users of reporting on environmental activities of the enterprise. Therefore, environmental accounting requires a detailed study that will form a coherent system of this type of accounting in the world and as a result will improve the environmental situation on the planet. A novelty is the definition of prospects for the introduction of environmental accounting in Ukraine and its importance for the activities of enterprises. The article considers the historical preconditions for the emergence of environmental accounting and the definition of its essence. The information on ways of introduction of the ecological account, the possible plan of accounts, components of the ecological reporting is opened, the questions of the account of ecological expenses are considered. Ukraine’s measures to preserve the environment are highlighted and the prospects for the introduction of environmental accounting in the country are described.